Application technology of the sex pheromone of the tea geometrid Ectropis grisescens (Lepidoptera: Geometridae). Issue 4 (2nd October 2018) - Wang, Zhibo; Ma, Tao; Mao, Tengfei; Guo, Huawei; Zhou, Xiaogui; Wen, Xiujun; Xiao, Qiang
ABSTRACT: The sex pheromone of Ectropis grisescens, one of the primary defoliator insects of tea plantations, has been identified, but its trapping parameters have not been optimized for field application. In this study, we investigated the effects of pheromone dose, trap height and trap type on the effectiveness of trapping E. grisescens in the field. Our results show that the optimal pheromone dose is 800 μg. The bucket-funnel trap hung 40 cm below the tea canopy had the highest trapping efficiency. This study establishes optimized parameters for the pheromone trapping of E. grisescens in tea plantations.